BAP1 links metabolic regulation of ferroptosis to tumor suppression - Zhang, Yilei (Nat Cell Biol, 2018)
The roles and regulatory mechanisms of ferroptosis, a non-apoptotic form of cell death, in cancer remain unclear. The tumor suppressor BRCA1-associated protein 1 (BAP1) encodes a nuclear de-ubiquitinating (DUB) enzyme to reduce histone 2A ubiquitination (H2Aub) on chromatin. Here integrated transcriptomic, epigenomic, and cancer genomic analyses link BAP1 to metabolism-related biological processes, and identify cystine transporter SLC7A11 as a key BAP1 target gene in human cancers. Functional studies reveal that BAP1 decreases H2Aub occupancy on the SLC7A11 promoter and represses SLC7A11 expression in a DUB-dependent manner and that BAP1 inhibits cystine uptake through repressing SLC7A11 expression, leading to elevated lipid peroxidation and ferroptosis. Furthermore, we show that BAP1 inhibits tumor development partly through SLC7A11 and ferroptosis and that cancer-associated BAP1 mutants lose their abilities to repress SLC7A11 and to promote ferroptosis. Together, our results uncover a previously unappreciated epigenetic mechanism coupling ferroptosis to tumor suppression.